Assessment of Outdoor Radiation Exposure in an Academic Environment: A Case Study of Lead City University - Rhoda I. ADELAJA; Ruth R. ADELAJA; Henry OTOBRISE; Adefope OWOJORI; Babatunde ADEBO (FUDMA Journal of Engineering and Technology, 2025)
This study presents an assessment of outdoor gamma background ionizing radiation across selected locations within Lead City University, Ibadan, South-western Nigeria, using a Gamma-Scout survey meter. Five radiological parameters were evaluated: equivalent dose rate (EDR), absorbed dose rate (ADR), annual effective dose equivalent (AEDE), excess lifetime cancer risk (ELCR), and effective dose rate to organs (Dorgan). All surveyed sites recorded EDR values exceeding the International Commission on Radiological Protection (ICRP) recommended limit of 0.133 μSv/h, with the lowest value observed at CPG (0.17 μSv/h) and the highest at SFB1 (0.25 μSv/h). ADR values also surpassed the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) global average of 55 nGy/h, ranging from 170 nGy/h at CPT1 and CPG to 250 nGy/h at SFB2. Although background radiation levels were elevated, AEDE values remained below the ICRP annual threshold of 1 mSv/y, averaging 0.25 mSv/y. The lowest AEDE was recorded at CPT1 and CPG (0.21 mSv/y), while SFB2 showed the highest (0.31 mSv/y). ELCR values ranged from 0.73 × 10⁻³ to 1.07 × 10⁻³, exceeding the global average of 0.293 × 10⁻³, indicating a slightly increased lifetime cancer risk. In contrast, Dorgan values were significantly lower than the global average of 1 mSv/y, with a mean of 0.07 mSv/y across all locations. Overall, the findings suggest localized elevation in environmental radiation, potentially influenced by geological or material-specific factors. While short-term exposure levels exceed global norms, the relatively low AEDE and Dorgan values imply that immediate health risks such as acute radiation effects or organ damage are unlikely. These results emphasize the importance of continuous environmental monitoring and localized radiological risk evaluation to safeguard public health.